Understanding employment systems from a gender perspective: pitfalls and potentials of new comparative analytical frameworks - Karin Gottschall; Karen A. Shire (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2007)
Economic globalization, welfare state transformation as well as political and social change on national and supranational level impact on national labor markets in advanced societies in complex ways. From a gender perspective, these dynamics of change entail deregulation as well as re-regulation of employment systems and at the same time are triggered by shifts in gender relations. Addressing this complexity poses challenges to scholarly research comparing employment systems and systemizing cross-national variations of labor market regimes which tend to neglect gender relations as a relevant factor of change. This context sets the framework for our question on how ongoing changes in employment systems and in gender relations are taken up in recent scholarship. We focus on three approaches prominent in the mainstream scholarly debate which address the current state of employment systems in advanced economies in comparative perspective spanning from political economy to micro economics and economic sociology, namely the Varieties of Capitalism (VOC) approach (Hall/Soskice 2001), Marsden's micro-economic theory of employment systems (1999) and Fligstein's work 'The architecture of markets' (2001). The approaches differ in the assignment of agency (to firms, employees and the state) as well as in the assessment of the role of educational institutions for shaping employment systems. They thus dispose of different pitfalls and potentials for analyzing the gendered character of change of employment systems. – – Unter dem Einfluss von Globalisierung, Wohlfahrtsstaatstransformation und politischen und gesellschaftlichen Umbrüchen sind nationale Arbeitsmärkte in fortgeschrittenen Marktökonomien erheblichen Veränderungen ausgesetzt. In geschlechtssensibler Perspektive wird deutlich, dass hier nicht nur Deregulierung von Beschäftigung sondern auch Re- Regulierung eine Rolle spielt, ebenso wie Arbeitsmarktdynamiken auch durch Veränderungen im Geschlechterverhältnis beeinflusst sind. Diese Komplexität des Wandels stellt eine Herausforderung für die vergleichende Arbeitsmarkt- und Wohlfahrtsstaatsforschung dar, in deren Typisierung von Arbeitsmarktregimes Geschlechterverhältnisse nur begrenzt Berücksichtigung finden. Vor diesem Hintergrund fragen wir, wie in einschlägigen neueren Ansätzen zur Analyse von Arbeitsmärkten Wandel von Beschäftigungssystemen und Geschlechterverhältnissen konzipiert wird. Im Mittelpunkt stehen drei prominente komparatistisch ausgerichtete Konzepte: der polit-ökonomische Ansatz 'Varieties of Capitalism' (Hall/Soskice 2001), die mikro-ökonomische Theorie von Beschäftigungssystemen von David Marsden (1999) und Neil Fligstein's wirtschaftssoziologischer Ansatz 'The architecture of markets' (2001). Wie die Ergebnisse zeigen, unterscheiden sich die Ansätze in der Identifikation von relevanten Akteuren (Betriebe, Beschäftigte, Staat) ebenso wie in der Rolle, die Ausbildungsinstitutionen für die Strukturierung von Arbeitsmärkten zugeschrieben wird. Damit ergeben sich für die Analyse von geschlechtsspezifischen Aspekten von Beschäftigung unterschiedliche blinde Flecken und Erkenntnispotentiale.
Keywords: 320; Arbeitsmarkt; Sozialstaat; Geschlecht; Wissenschaftstheorie; Theorie